Peran Pemasaran Media Sosial Terhadap Keputusan Pembelian Melalui Kepercayaan - Sitanggang, Natashya Ketrine; Tjiptodjojo, Kartika Imasari (Forum Kerjasama Pendidikan Tinggi, 2025)
With the development of the times, smoking habits for many people have changed. Many people use e-cigarettes, one of which is an e-cigarette with the Foom brand. Many consumers use e-cigarettes for the reason of reducing smoking habits. The existence of e-cigarettes also affects the desire to buy from many people, where most people purchase e-cigarettes because they get much information from social media. A total of 110 respondents were taken as samples with the criteria of being over 18 years old, active users of e-cigarettes, and active social media users. Data testing was carried out through path tests and the results found that social media marketing and trust influenced purchasing decisions by 49.4%. However, trust does not influence purchasing decisions, and also trust does not mediate between social media marketing and purchasing decisions.